Ploidy level and nuclear DNA content of some acceáions of water yam (Dioscorea alata) collected at Save, a district of ceentral Benin - Dansi, A.=700 1 Dainou, O.; Agbangla, C.; Ahanhanzo, C.; Brown S.; Adoukonou-Sagbadja, H.
(Es, En, Fr)
ilus., 31 ref.
Keywords: DIOSCOREA ALATA; ADN; NUMERO DE CROMOSOMAS; BENIN; ÑAME DE AGUA